I Watched You Disappear : Poems - Silver, Anya Krugovoy, 1968-2018 (Book collections on Project MUSE., 2014)
Passionately written and perfectly crafted, Anya Krugovoy Silver's poems help us to view life through a different lens. In I Watched You Disappear, she offers meditations on sickness but also celebrations of art, motherhood, and family, as well as a sequence of poems based on the fairy tales of the Brothers Grimm. Throughout her collection, Silver examines feelings of pain, anger, and urgency caused by a serious illness and presents the struggle to cope in a lyrical and moving way. Never overwhelmed by her own mortality, Silver manages to speak with beauty and grace about a terrifying subject.